Innovative Ideas For Madrasah Development Management - Cempaka, Viola (Lentera Ilmu Nusantara, 2025)
This study aims to identify and analyze innovative ideas in Islamic educational management relevant to the challenges and dynamics of the 21st century. The focus is on the integration of digital technology, value-based curriculum approaches, and transformative leadership models in Islamic educational institutions. This research uses a qualitative literature review method with content analysis techniques. The results indicate that Islamic educational management can be enhanced through strengthening the vision of madrasa digitalization, multi-stakeholder collaboration, and the development of human resources oriented towards both spiritual and professional competence. These findings have strategic implications for developing adaptive and sustainable Islamic education policies.